Bioengineered Gastrointestinal Tissues with Fibroblast‐Induced Shapes. (25th November 2020) - Zhou, Linna; Ruiz‐Puig, Carlos; Jacobs, Brittany‐Amber; Han, Xiaoyue; Lisle, Richard; Bayley, Hagan; Lu, Xin
Abstract: Bioengineered gastrointestinal (GI) tracts have potential applications in regenerative medicine and disease modeling. Methods for engineering tubular GI tracts containing natural extracellular matrix (ECM) are currently limited. Here, the fabrication of collagen tubes with designed shapes by using lipid bilayer supported droplet networks is reported. Droplets containing cells and collagen are arrayed in lipid‐containing oil to form droplet networks, which undergo thermal gelation to provide continuous collagen tubes. A variety of tubular GI tissues are fabricated. For example, human intestinal organoids embedded in the collagen tubes migrate to the luminal surfaces and fuse to form a continuous epithelial layer, mimicking aspects of intestinal tissue structure. Fibroblasts embedded in the collagen induce a cell density dependent contraction of the tubes. Complex tubular structures are produced by patterning droplets containing different densities of fibroblasts. The fibroblast‐containing collagen tubes are seeded with various epithelial cells at their luminal surfaces to form gastric and colonic tissues, which comprise monolayers or multilayers of epithelial cells and fibroblast‐containing subepithelial layers. The engineered gastric tissues are susceptible to infection with Helicobacter pylori . The versatile technique allows the construction of tubular GI tracts containing ECM and layered structures, with broad potential applications in disease research and regenerative medicine. Abstract : Bioengineered gastrointestinal (GI) tracts have potential applications both in regenerative medicine and disease modeling. The method reported here produces collagen tubes with designed shapes by using lipid bilayer supported droplet networks. Complex shapes are generated by controlling the seeding density of fibroblasts. Further, when seeded with fibroblasts and epithelial cells, the tubular structures form subepithelial and epithelial layers that line their lumens.